Prevalence of Brugada-type electrocardiogram pattern by recording right precordial leads at higher intercostal spaces - KEPEZ, ALPER; ERDOĞAN, OKAN (OXFORD UNIV PRESS, 2013)
Recording electrocardiograms (ECGs) by placing the right precordial leads at higher intercostal spaces (ICSs) increases the sensitivity for detecting Brugada-type ECG pattern (BTEP). Published studies unfortunately used standard lead positions for recording ECGs and underestimated the true prevalence of BTEP. Therefore, by placing right precordial leads at higher ICS, we aimed to find out the true prevalence of BTEP in our population. Healthy male volunteers (n 504) between 18 and 55 years of age (37.3 10.7 years) without known cardiac or metabolic disorders were enrolled into the study. After the standard ECG recording, two other recordings were obtained by placing the right precordial leads to the third and second ICS. Electrocardiograms were stratified by two independent reviewers for the presence of BTEP. There were 15 subjects (3) who displayed BTEP on their standard ECG recordings. Number of cases displaying BTEP increased to 25 (5) and 38 (7.5) when the right precordial leads were moved to third and second ICS, respectively. Although none of the subjects displayed type 1 BTEP on their standard ECGs, three subjects displayed type 1 BTEP on the third and four subjects displayed type 1 BTEP on the second ICS. Our study revealed that the prevalence of BTEP in healthy male subjects was 7.5 by placing the right precordial leads to higher ICS. Instead of standard lead locations that are not sensitive enough for detection of BTEP we recommend high right ICS recording in further prevalence studies.
Keywords: Brugada syndrome; Brugada pattern; Prevalence; ECG; Diagnosis; Epidemiology; ST SEGMENT ELEVATION; BUNDLE-BRANCH BLOCK; ECG PATTERN; FOLLOW-UP; SIGN; POPULATION; PROGNOSIS; MALES; 3RD